Research on improving the registration success rate of VoWi-Fi under multiple equivalent path scenarios - Deyi CHENG; Jian QIAO (Dianxin kexue)
The 3GPP's VoWi-Fi S2b specification requires the client to use the IPSec tunnel to register with the ePDG through the metropolitan area network. When IPSec faces a path forwarding fault in a multi-equivalent path environment of a metropolitan area network, it can't actively evade, and the service can't be registered. The cause of the malfunction was analyzed and an optimized solution was proposed. By changing the client source port in the IKE_AUTH phase to achieve path replacement, the VoWi-Fi registration success rate can be significantly improved and verified by experiments. Secondly, through the full traversal detection of the bidirectional network path between the edge of the metropolitan area network and the ePDG end, the fault can be quickly located and eliminated.